On-Site Analysis of Bacterial Communities of the Ultraoligotrophic South Pacific Gyre - Reintjes, Greta (Appl Environ Microbiol, 2019)
The South Pacific Gyre (SPG) covers 10% of the ocean’s surface and is often regarded as a marine biological desert. To gain an on-site overview of the remote, ultraoligotrophic microbial community of the SPG, we developed a novel onboard analysis pipeline, which combines next-generation sequencing with fluorescence in situ hybridization and automated cell enumeration. We tested the pipeline during the SO-245 “UltraPac” cruise from Chile to New Zealand and found that the overall microbial community of the SPG was highly similar to those of other oceanic gyres. The SPG was dominated by 20 major bacterial clades, including SAR11, SAR116, the AEGEAN-169 marine group, SAR86, Prochlorococcus, SAR324, SAR406, and SAR202. Most of the bacterial clades showed a strong vertical (20 m to 5,000 m), but only a weak longitudinal (80°W to 160°W), distribution pattern. Surprisingly, in the central gyre, Prochlorococcus, the dominant photosynthetic organism, had only low cellular abundances in the upper waters (20 to 80 m) and was more frequent around the 1% irradiance zone (100 to 150 m). Instead, the surface waters of the central gyre were dominated by the SAR11, SAR86, and SAR116 clades known to harbor light-driven proton pumps. The alphaproteobacterial AEGEAN-169 marine group was particularly abundant in the surface waters of the central gyre, indicating a potentially interesting adaptation to ultraoligotrophic waters and high solar irradiance. In the future, the newly developed community analysis pipeline will allow for on-site insights into a microbial community within 35 h of sampling, which will permit more targeted sampling efforts and hypothesis-driven research. IMPORTANCE The South Pacific Gyre, due to its vast size and remoteness, is one of the least-studied oceanic regions on earth. However, both remote sensing and in situ measurements indicated that the activity of its microbial community contributes significantly to global biogeochemical cycles. Presented here is an unparalleled investigation of the microbial community of the SPG from 20- to 5,000-m depths covering a geographic distance of ∼7,000 km. This insight was achieved through the development of a novel onboard analysis pipeline, which combines next-generation sequencing with fluorescence in situ hybridization and automated cell enumeration. The pipeline is well comparable to onshore systems based on the Illumina platforms and yields microbial community data in less than 35 h after sampling. Going forward, the ability to gain on-site knowledge of a remote microbial community will permit hypothesis-driven research, through the generation of novel scientific questions and subsequent additional targeted sampling efforts.